The Role Of Local Wisdom Of Dana Mbojo In Climate Change Mitigation: Analysis Of The Parafu System And Pamali Practices - Nurrahmania, Nurrahmania; Fahruddin, Fahruddin; Azmin, Nikman; Putra, Anggar (UNIVERSITAS PAKUAN, 2025)
This study examines the role of local wisdom of the Dana Mbojo community in climate change mitigation, focusing on the Parafu system (customary land management patterns) and Pamali practices (customary prohibitions related to environmental conservation). The urgency of this research lies in the need for a culturally based approach to strengthen climate change mitigation strategies that have been dominated by technocratic approaches. This study aims to identify and analyze the contribution of the Parafu system and Pamali practices to forest, water, and soil conservation, and assess their relevance in the context of climate change adaptation. The study used mixed methods with qualitative and quantitative approaches. Data collection techniques included in-depth interviews with 25 traditional and community leaders, field observations in three traditional villages, and the distribution of questionnaires to 150 respondents, which were analyzed using descriptive statistics. The results showed that the Parafu system contributed to a decrease in deforestation rates by 18.3% in the last five years, while Pamali practices were effective in reducing land burning activities by up to 27.6% compared to non-customary areas (p=0.003). Eighty-four percent of respondents stated that the application of customary values can maintain the balance of local ecosystems, and 76% stated that customary law is more adhered to than formal government regulations. The local wisdom of Dana Mbojo, through the Parafu system and Pamali practices, has great potential for climate change mitigation, particularly through social control mechanisms, value-based conservation, and sustainable spatial use. Integrating local values into climate mitigation policies at the regional and national levels is a strategic step that needs to be implemented immediately.